Medeia: alegorias da resistência em Antônio José da Silva e Pier Paolo Pasolini - Melo, Lucas Gilnei Pereira de (2020)
This thesis aims to analyze the character Medeia, from the play Encantos de Medeia, by the Portuguese-Brazilian comedian Antônio José da Silva, the Jew, and his homonymous film version of Pier Paolo Pasolini, as allegories of resistance in the following periods: Inquisition in Portugal in the 18th century and Italian neo-fascism in the 1960s and 1970s. In first writer, Medeia denounces Lisbon's inquisitorial machinery. Therefore, the film version helps to criticize the remnants of censorship and conservatism from the Italian neo-fascist period. In both, the figure of the tragic sorceress stands out, over the centuries and being reinvented in different temporalities, above all because it represents not only hybris, tragic and passionate love, but also being an allegory of confrontation against authoritarianism, patriarchy and to male chauvinist, which rose and still rise, under the aegis of political and religious persecution. Our research is divided into three chapters. First, we will do a biographical rescue of the artists, checking, mainly, points that interconnect them, besides the reasons that made them be persecuted. In this chapter, the point that instigates us is the institution or system of power that rejoices with the death of the poet, both literal and cultural, making them marginalized, excluded subjects and hindering their survival. In the second chapter, in a historical survey, we approached the Inquisition, Fascism and Neofascism, extended after the deposition of Mussolini in 1940, with a wave of extreme right politicians, supported by a good part of the population. In the third and final section, we will analyze the adaptations of the character Medeia by Antônio José da Silva and Pier Paolo Pasolini, verifying the extent to which the texts denounce and clash with the regimes of the time, making allegorical confrontations with misogynistic persecutions, censorship attacks and to religious and political institutions. Although Antônio José's Medeia is light and romantic, his character stands out at a time in history when thousands of women were taken to the fires of the Inquisition. Pasolini's character, on the other hand, masterfully embodies the tragic Euripidian spirit, as it reveals his barbaric and foreign origin.